The library catalogue as social space [ promoting patron driven collections, online communities, and enhanced reference and readers' services - Tarulli, Laurel (Libraries Unlimited, 2012)
"Emphasizing the advantages of working together and exploring the future of library services in an online, socially connected world, this exciting book shows how all public library professionals can take advantage of our strongest community and information tool--the library catalogue"--Provided by publisher